Estudo técnico de um transportador de correia - Rigolo, Leonardo Visentainer [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The belt conveyor began to be used in England from the second half of the eighteenth century, with the passage of time and the development of new technologies the conveyor belt began to be used in different applications. Nowadays several industries use this equipment due to its low cost, versatility, reliability and high capacity of transport. This work aims to show the reader what a belt conveyor is, explaining its main mechanical components, some of which are mandatory for its operation and others that are used depending on the application of the belt conveyor. Subsequently, it will be demonstrated the dimensioning of the conveyor through basic calculations covering topics such as belt selection, roller selection, calculation of the load applied to the rollers, calculation of the maximum and minimum speed of the belt, calculation of the effective force on the belt, verification of the deflection of the belt. belt selection, maximum and minimum belt force calculation, drum diameter selection, engine power calculation and through selection of belt selection and selection of the reduction motor. The conveyor in question will be used for a crushing industry, but the calculations can be applied for the transport of other types of material. For small conveyors the sizing through the presented concept is valid, however for large conveyors a dynamic analysis is required, through the use of others methods. It is essential to simulate static and dynamic loads for these structures

O transportador de correia começou a ser utilizado na Inglaterra a partir da segunda metade do século XVIII, com o passar do tempo e o desenvolvimento de novas tecnologias o transportador de correia começou a ser utilizado em diferentes aplicações. Hoje em dia diversas industrias utilizam esse equipamento devido ao seu baixo custo, versatilidade, confiabilidade e elevada capacidade de transporte. Este trabalho visa mostrar ao leitor o que é um transportador de correia, explicando os seus principais componentes mecânicos, sendo alguns obrigatórios para o seu funcionamento e outros que são utilizados dependendo de sua aplicação. Posteriormente irá ser mostrado o dimensionamento do transportador através de cálculos básicos abordando tópicos como seleção da correia, seleção dos roletes, cálculo da carga aplicada nos roletes, cálculo da velocidade máxima e mínima da correia, cálculo da força efetiva na correia, verificação da deflexão da correia, cálculo da força máxima e mínima na correia, seleção do diâmetro dos tambores, cálculo da potência do motor e através de catálogos serão feitas a seleção da correia e a seleção do moto redutor. O transportador em questão será utilizado para uma indústria de britagem, porém os cálculos podem ser aplicados para o transporte de outros tipos de materiais. Para transportadores de pequeno porte o dimensionamento através do conceito apresentado é valido, porém para transportadores de grande porte é necessária uma análise dinâmica, através da utilização de outros métodos. Sendo imprescindível a simulação de cargas estáticas e dinâmicas para essas estruturas
Technical study of a belt conveyor
Keywords: Correias transportadoras; Desenho (Engenharia); Correias e transmissão por correias; Conveyor belts